A pilot project at the Paper Money Museum, Porto (Portugal) - Semedo, Alice (2014)
This paper will outline models and strategies in education and partnerships with neighbouring schools developed by the Paper Money Museum during the past year. The museum is well-known for its inclusive approach to different audiences and is currently trying to develop educational school programmes which involve the building of different relationships with schools and community advocates as well as the development of ongoing research about not only representations and outlooks but also about the outcomes of such projects. The analysis and discussion of data produced by this research and its relation to the building of new education models for this museum constitutes the core theme of this paper